2016
DOI: 10.17221/778/2015-pse
|View full text |Cite
|
Sign up to set email alerts
|

Effect of application of growth regulators on the physiological and yield parameters of winter wheat under water deficit

Abstract: The objective of this study was to evaluate the effect of growth regulator applications on yield and physiological parameters of winter wheat (Triticum aestivum L.) under water deficit. Water deficit was induced artificially by using rain-out shelters in period between booting and late milk ripeness. The effect of growth regulators was evaluated in two contrast years in terms of yield formation (2014)(2015). In both years the water deficit caused a significant reduction of grain yield. The negative effect of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 17 publications
1
8
1
Order By: Relevance
“…AZ is a fungicide for control crop diseases and is also considered as a growth regulator that would recover CO 2 assimilation rate and stomatal conductance [ 21 ]. Additionally, the application of AZ increased water use efficacy, cell membrane stability, enzymatic antioxidant systems (catalase, peroxidase, polyphenol oxidase), total phenols, root growth to improve drought tolerance, and fruit yield in tomato [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…AZ is a fungicide for control crop diseases and is also considered as a growth regulator that would recover CO 2 assimilation rate and stomatal conductance [ 21 ]. Additionally, the application of AZ increased water use efficacy, cell membrane stability, enzymatic antioxidant systems (catalase, peroxidase, polyphenol oxidase), total phenols, root growth to improve drought tolerance, and fruit yield in tomato [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study revealed that exogenous AZ inhibited photochemical and photo-protection parameters and led to severe photodamage in wheat seedlings under heat stress [ 39 ]. Barányiová and Klem [ 21 ] also indicated that the application of AZ during drought was unconducive to chlorophyll fluorescence because of reduced stomatal conductance and blocked gas exchange in wheat that was not infected by fungus. The recommended concentration of AZ application in tea gardens is 0.125 g L −1 with a 21-day pre-harvest interval in Taiwan, therefore 0.125 and 1.25 AZ g AZ L −1 were applied in this study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations